Conceptual Metaphors in A Collection of Cirebon Folklore by Made Casta and Masduki Sarpin - Afina Naufalia; Tajudin Nur; Sutiono Mahdi; Agus Suherman Suryadimulya (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
This research is motivated by themetaphorical language that often appears in literary works because literary works contain many connotative meanings, so they use majas. One of the literary works is folklore. In this study, researchers were interested in analyzing conceptual metaphors found in several folklore. The source of the research used is based on a collection of folklore entitled